Akibat Hukum Perjanjian Perdagangan Bebas Di Asean Indonesia-Malaysia - Meher, Montayana; Rafiqi; Nasution, Shulhan Iqbal; Nasution, Alvin Hamzah (Jurnal Ilmiah Penegakan Hukum, 2024)
This research aims to find out how international trade agreements are basically used by countries and producers to eliminate or reduce barriers in countries with consumers and markets. However, this condition is used as an excuse for free trade that does not comply with proper trading rules and patterns. The research method used is normative juridical research. The nature of this research is descriptive, namely research that analyzes legal regulations related to the Free Trade Agreement in ASEAN between Indonesia and Malaysia. The analysis was carried out qualitatively. The research results show that cooperation and economic integration among member countries has great potential to encourage economic growth and expand trade opportunities. Although there are still several obstacles that need to be overcome, such as internal and external factors that influence the competitiveness of Micro, Small and Medium Enterprises (MSMEs), the steps taken by ASEAN in terms of exemption from import duties through CEPT are one of the efforts to increase integration regional economy. Addressing internal factors that influence innovation and productivity, and integrating MSMEs in regional or global production chains will be key to maximizing trade potential and economic growth among ASEAN countries, including Indonesia and Malaysia. And the need to understand the dynamics of global trade, international economic policy, and changes in regional trade patterns